A role for the canonical nuclear factor-κB pathway in coupling neurotrophin-induced differential survival of developing spiral ganglion neurons - Vandenbosch, Renaud; Chocholova, Eva; Robe, Pierre; Wang, Yiqiao; Lambert, Cecile; Moonen, Gustave; Lallemend, Francois; Malgrange, Brigitte; Hadjab, Saida (Frontiers in Cellular Neuroscience, 2013)
Neurotrophins are key players of neural development by controlling cell death programs. However, the signaling pathways that mediate their selective responses in different populations of neurons remain unclear. In the mammalian cochlea, sensory neurons differentiate perinatally into type I and type II population both expressing TrkB and TrkC, which bind respectively brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT3). How these two neuronal populations respond differentially to these two neurotrophins remains unknown. Here, we report in rat the segregation of the NFκB subunit p65 specifically within the type II population postnatally. Using dissociated cultures of embryonic and postnatal spiral ganglion neurons, we observed a specific requirement of NFκB for BDNF- but not NT3-dependent neuronal survival during a particular postnatal time window that corresponds to a period of neuronal cell death and hair cell innervation refinement in the developing cochlea. Consistently, postnatal p65 knockout mice showed a specific decreased number in type II spiral ganglion neurons. Taken together, these results identify NFκB as a type II neuron-specific factor that participates in the selective survival effects of BDNF and NT3 signaling on developing spiral ganglion neurons.